Sb/Bi based perovskite X-ray detectors - Foo, Norton Di Kai (Nanyang Technological University, 2023)
X-ray detection is one of the most extensive detection field due to its broad demand and applications in many aspects of sciences. Generally, two different strategies exist for X-ray conversion and detection. For direct conversion, highly energetic X-rays photons were directly converted into electrical signals in the detector, while indirect conversion relied on converting incoming X-rays into lower energy UV-visible photons that were detected by photosensors subsequently. Metal halide perovskites (MHPs) and single crystal perovskites (SCPs) are established compounds for X-ray detection and energy conversion applications due to their high average atomic number (Z), carrier mobility-lifetime product (μt), absorption efficiency, radiation resistivity (r) and low detection limit and trap densities functions. SCPs possesses unique continuous unbroken crystal lattices due to the prominent absence of grain boundaries. For scintillation detectors, thicker SCPs could enhance stopping power by completely attenuating incoming high energies X-rays and promoting light emission with increase crystal transparency and reduced scattering. Furthermore, faster radiation recombination speed is imperative to reduce response time during X-ray conversion. For semiconducting detectors, the separation of octahedral sheets by organic spacer in 2D MHPs could contribute to stronger structural compatibility, reduction in self-trapping and higher ambient stability in the semiconducting material, thereby reducing ion migration and promoting carrier diffusion and recombination of electron-holes pairs. Currently, lead-halide perovskites (LHPs) are highly regarded as new possibilities for detection materials. However, the malignant nature of lead (Pb) towards living organisms and the natural environment motivated studies to develop lead-alternative perovskites suitable for X-ray detection. One popular method is to substitute Pb with similar 6s2 electronic configuration elements such as antimony (Sb) and bismuth (Bi). SCPs of Cs3Sb2I9 and Cs3Bi2I9 form low dimensional (0D) MHPs hexagonal crystal structures with space group P63/mmc. However, Cs3Sb2I9 could also form another more stable, 2D layered polymorph with space group P3"m1. Despite their advantages, ii attempts to grow SCPs of Cs3Sb2I9 and Cs3Bi2I9 via hydrothermal procedures have not been attempted nor initiated. In this work, SCPs of Cs3Sb2I9 and Cs3Bi2I9 were grown using the hydrothermal method. Using this method, micron sized (1) bright red Cs3Sb2I9 SCPs and (2) dark red Cs3Bi2I9 SCPs that crystallizes in the 0D dimer polymorph hexagonal crystal structure with space group P63/mmc could be obtained. SCPs produced in this study have uniform elemental distribution across each SCPs and verified atomic ratios of Cs3Sb2I9 to be 3.00 : 2.07 : 9.00, and 3.00 : 2.02 : 9.36 for Cs3Bi2I9 SCPs respectively, further suggesting their suitability for SCPs scintillator detectors. Moreover, with a bandgap of 1.97 eV and 1.89 eV for Cs3Sb2I9 and Cs3Bi2I9 SCPs respectively, both compounds could also be employed as materials for semiconducting detectors since they have bandgaps that are comparable with existing semiconducting materials and detectors, along with characteristics such as high Z and μt etc. exhibited in MHPs employed in semiconducting fields including photovoltaics and optoelectronics.